Patogenisitas Entomopatogen Beauveria bassiana (Bals.) Vuill. Terhadap Larva Crocidolomia pavonana (F.) pada Tanaman Kubis (Brassica oleracea var. capitata) di Laboratorium - Moningka, Cinthya Eleita; Lengkong, Maxi; Kandowangko, Daisy Sandra (JURNAL ENFIT : Entomologi dan Fitopatologi, 2025)
Crocidolomia pavonana is an important pest on cabbage plants. The use of biological control agents such as the entomopathogenic fungus Beauveria bassiana is an alternative to control C. pavonana. This study aims to determine the pathogenicity of the entomopathogenic fungus B. bassiana with a certain density of conidia on the mortality of C. pavonana larvae based on LT50 and LC50 tests.This research was conducted in vitro using a completely randomized design (CRD). With a treatment level of 4 treatments and 3 replications. The number of samples per repetition is 10 larvae and the total sample in one treatment is 30 larvae. Treatment experiments used variations in concentration of B. bassiana conidia density, namely conidia density of 108 conidia/ml (A), 107 conidia/ml (B), 106 conidia/ml (C), and Control (K). The pathogenicity of the entomopathogenic fungus B. bassiana can infect C. pavonana larvae from one day after application. The density concentration of 108 conidia/ml is very good and can cause 100% mortality on the eighth day. The fastest LT50 value was in the treatment with a density of 108 conidia/ml, while the LC50 value was found in a concentration with a density of 108 conidia/ml.